Have Federal Sentencing Guidelines Reduced Severity? An Examination of One Circuit - Kempf Leonard, Kimberly (Journal of quantitative criminology, 2001)
Congress intended to make the sentencing process less discretionary and more equitable for similarly situated defendants when it passed the U.S. Sentencing Reform Act of 1984. Sentencing guidelines were devised to promote these changes. After more than a decade of implementation, however, little is known about the impact of the new policy. This paper examines sentences given between 1993 and 1994 in one federal circuit in an effort to determine whether this policy instrument has achieved success. The theoretical model of a rational case processing system (Gottfredson and Gottfredson, 1980) is used to guide the interpretation of our findings and the recommendations we offer for improvements.